Soil organic carbon decomposition pattern in some agroforestry systems in Bundelkhand Region of Central India - Prasad, Rajendra; Newaj, Ram; Saroj, N.K.; Tripathi, V.D.; Dhyani, S.K. (Indian Journal of Agroforestry, 2020)
Estimates of soil organic carbon (SOC) decomposition of different agroforestry systems are important for establishing role of agroforestry in carbon sequestration and mitigation of global climate change. The dynamics of soil organic carbon decomposition was studied in Hardwikia binata Roxb, Embilica officinalis Gaertn. and Acacia SenegalÂ (L.) Willd based agroforestry systems, and open crop field. A 90- dayâ€™s laboratory incubation was conducted to measure CO2 evolution from soil of different agroforestry systems and open crop field. SOC decomposition rates were different in different agroforestry systems; however, qualitative trends remained similar with rapid decomposition in the initial stages, which gradually slowed down to a steady state. Short duration of rapid decomposition owned a large quantity of decomposition, while slow decomposition owned relatively smaller quantity but took a long time. The share of SOC decomposition in the first week accounted for 43.2 to 65.2% of total SOC decomposition. In different agroforestry systems, the total release of CO2-C varied from 265.1 to 452.6 mg CO2-C/kg soil accounting 4.1 to 8.0% of SOC. Maximum fraction of total SOC was mineralized in open crop field (8.0%), while minimum in H. binata (black soil) based agroforestry system (4.1%). On an average, rate of decomposition of SOC was more in open crop field than agroforestry system at initial stage of incubation. In terms of percentage of total SOC mineralization, the order of different agroforestry systems was H. binata (red soil) > A. senegal > E. officinalis > H. binata (black soil).